Bridge management 3 inspection, maintenance, assessment, and repair - Harding, John E.; Parke, G.A.R; Ryall, M.J (E & FN Spon, 1996)
This volume contains the papers presented at the Third International Conference on Bridge Management, held at the University of Surrey, Guildford, UK on 14-17 April 1996.